Draft Annual Plan 1985-86 Vol. - II Government of Tripura - Planning Commission (Planning Commission, 1985)
The over all objective of annual plan 1985-86 is to increase production of all important agricultural crops in the State within the objective of the 7th Five Year Flan. There is practically no scope for extending area under field crops by bringing new areas. It is, therefore, proposed to achieve the increase in agricultural production through intensive cultivation by way of increasing cropping intensity through adoption of multi-cropping by popularising suitable cropping sequence for increasing multiple cropping and also by increasing consumption of different productive inputs.
Government of Tripura